Microrna Profiling of Serum Exosomes in Patients with Osteosarcoma by High-Throughput Sequencing. (April 2020) - Ye, Zhimeng; Zheng, Zhuojun; Peng, Linrui
The microRNA expression profile of plasma exosomes in osteosarcoma needs to be further explored. The present study intends to investigate the practicality of plasma exosomal miRNAs as novel biomarkers of osteosarcoma. In the study, exosome-like vesicles were purified from the plasma of patients with osteosarcoma and healthy control. Differential centrifugation was used. The purified vesicles which ranged from 50 to 100 nm in size were identified as exosomes by transmission electron microscopy and western blot. Validating assays in vitro and in vivo were performed via CCK8, reverse transcription-quantitative PCR, flow cytometry, transwell and wound healing assays and xenograft model. High-throughput sequencing identified that 57 miRNAs, 20 of which were upregulated and 37 downregulated, were differentially expressed in patients with osteosarcoma and healthy control (p<0.01; fold change ≥3). In comparison to the controls, the expression levels of miR-92a-3p, miR-130a-3p, miR-195-3 p, miR-335-5 p, let-7i-3p were upregulated in the exosomes from patients with osteosarcoma with statistical significance. Studies in vitro and in vivo have proved that osteosarcoma-secreted exosomes from miR-195-3 p upregulated 143B osteosarcoma cells promote cell proliferation and invasion. Overall, the present study identified exosomal miRNAs with dysregulated expression in patients with osteosarcoma, and they may have potential as targets for the treatment of patients with osteosarcoma.